The Effect of SAK EMKM Implementation on the Accuracy of Financial Statements - Samaria Simangunsong; Mira Agustia; Siti Zahara; Olivia Deslovita Ginting; Irawan (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
This study aims to determine the effect of EMKM SAK implementation on the accuracy of financial statements in Deli. The background of this study is based on the importance of accurate financial statements for business continuity, especially in terms of decision making and access to financing. However, there are still many businesses that have not implemented accounting standards appropriately in financial management. This study uses a quantitative approach with a survey method through the distribution of questionnaires, and the data is analyzed using the Partial Least Squares - Structural Equation Modeling (PLS-SEM) method with SmartPLS 4 software. The results of the study show that SAK EMKM has a positive and significant effect on the accuracy of financial statements. This finding confirms that improving understanding of accounting standards encourages the creation of accurate, reliable, and accountable financial reports. These results are important as a basis for SMES development policy making.